Application of Thomas-Fermi model to evaluation of thermodynamic properties of magnetized plasma - Kuzenov, V.V.; Ryzhkov, S.V.; Shumaev, V.V. (Вопросы атомной науки и техники, 2015)
The aim of this work is the evaluation of thermodynamic and transport properties of fusion plasmas in an externally applied strong magnetic field (10…103 T). For these purpose the Thomas-Fermi model for substances with a given temperature and density was used. The effect of such strong magnetic field on the transport properties of plasmas and the view of the inner shells of atoms and ions was analyzed. Isotherms of the pressure and the specific internal energy of the tungsten plasma are obtained. Quantum and exchange corrections to the pressure of this plasma have been taken into account. Определены термодинамические и транспортные свойства термоядерной плазмы, находящейся в сильном внешнем магнитном поле (10…1000 Тл). Для этой цели использовалась модель Томаса-Ферми для веществ с заданным температурой и плотностью. Проанализировано действие сильного магнитного поля на транспортные свойства плазмы и вид внутренних оболочек атомов и ионов. Построены изотермы давления, удельной внутренней энергии и энтропии плазмы вольфрама. Учтены квантовые и обменные поправки к давлению плазмы. Визначено термодинамічні і транспортні властивості термоядерної плазми, що знаходиться в сильному зовнішньому магнітному полі (10...1000 Тл). Для цієї мети використовувалася модель Томаса-Фермі для речовин із заданною температурою і щільністю. Проаналізовано дію сильного магнітного поля на транспортні властивості плазми і вид внутрішніх оболонок атомів і іонів. Побудовані ізотерми тиску, питомої внутрішньої енергії і ентропії плазми вольфраму. Враховані квантові і обмінні поправки до тиску плазми.